1996
DOI: 10.1080/01463379609370000
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive basis of gender communication: A cross‐cultural investigation of perceived constraints in requesting

Abstract: There has been a significant discussion regarding the similarities and differences in communication styles between females and males. If the stereotype is true that men use language "to assert a position of dominance" by coming directly to the point (clarity), whereas women use language to create and maintain relationships of closeness, this should be reflected in a differential preference for conversational constraints. Crosssituational goals (i.e., conversational constraints) serve as criteria for making a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Is the difference in language style then real or perceived? Kim and Bresnahan (1996), in a study of four cultures, found no differences in the communication goals of men and women. They stated that “perceived difference” resulting from stereotypes is much steeper than the “actual difference.”…”
Section: Discussionmentioning
confidence: 92%
“…Is the difference in language style then real or perceived? Kim and Bresnahan (1996), in a study of four cultures, found no differences in the communication goals of men and women. They stated that “perceived difference” resulting from stereotypes is much steeper than the “actual difference.”…”
Section: Discussionmentioning
confidence: 92%
“…Gray (1992Gray ( , 2002 failed to cite any empirical evidence (as it appears that he has not conducted any scientific research on the topic) to support his theories about specific communication characteristics, and his findings frequently conflict with reputable and scholarly research in these areas. For example, Kim and Bresnahan (1996) examined the determination of intention or motive behind verbal strategy choices, and found no significant differences between what men and women perceive as important in communication. Men and women, across four cultures, both found constraints such as interruptions and self-disclosure, to be important in communication behaviour.…”
Section: Studies Done In Other Countriesmentioning
confidence: 99%
“…Kim and Bresnahan (1996) examined the determination of intention or motive behind verbal strategy choices and found no significant differences in what men and women perceive as important in communication. The Bem's Sex Role Inventory (Wong, McCreary and Duffy, 1990) argues that men and women can and do develop attributes in both masculine and feminine gender domains.…”
Section: Studies That Contradict Gray (1992)mentioning
confidence: 99%